1996
DOI: 10.1074/jbc.271.34.20250
|View full text |Cite
|
Sign up to set email alerts
|

The Unpredicted High Affinities of a Large Number of Naturally Occurring Tachykinins for Chimeric NK1/NK3 Receptors Suggest a Role for an Inhibitory Domain in Determining Receptor Specificity

Abstract: Three chimeric receptors were constructed by exchanging exon sequences between human NK 1 and NK 3 receptor genes. The resulting chimeric receptors not only retained high affinities for their natural ligands substance P and neurokinin B but also exhibited surprisingly high affinities for other naturally occurring tachykinins including neurokinin A, neuropeptide K, neuropeptide ␥, eledoisin, kassinin, physalaemin, and phyllomedusin. In contrast, these chimeric receptors displayed a wide range of variability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…48 Using chimeric NK 1 and NK 3 receptors, Tian et al have shown that the C-terminal sequence of SP is important in determining binding affinities, while the N-terminal sequence seems to be more important in maintaining the appropriate conformation of the peptide for receptor binding and selectivity. 49 In this study we have shown that residues 4-9 of RTKA, RTKB, and RTKC exist in a similar conformation as determined in a SDS micelle system. This findings as well as the amino acid conservation supports the hypothesis that the biological activity and receptor binding to the bfSPR are confined to the C-terminus.…”
Section: Discussionmentioning
confidence: 71%
“…48 Using chimeric NK 1 and NK 3 receptors, Tian et al have shown that the C-terminal sequence of SP is important in determining binding affinities, while the N-terminal sequence seems to be more important in maintaining the appropriate conformation of the peptide for receptor binding and selectivity. 49 In this study we have shown that residues 4-9 of RTKA, RTKB, and RTKC exist in a similar conformation as determined in a SDS micelle system. This findings as well as the amino acid conservation supports the hypothesis that the biological activity and receptor binding to the bfSPR are confined to the C-terminus.…”
Section: Discussionmentioning
confidence: 71%
“…This diversification appears to have evolved by the emergence of inhibitory domains on both ligand and receptor which impose steric hindrances thus allowing only the intended ligand to interact with the common activation domain (28). Such negative specificity determinants have not only developed in glycoprotein hormones and their receptors, but also in other members of the cystine knot growth factor superfamily, such as neurotropins (29), and also in other G protein-coupled receptors (30). More generally, dimer formation is necessary for the activity and specificity of many, if not all cystine knot growth factors, as well as for other bioactive molecules, such as enzymes and transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an attempt to determine the basis of multiallelic self-incompatibility in plants was carried out by exchanging domains between allelic S-RNases from Nicotiana alata (39). Chimeric proteins have also been used to study proteinprotein interactions during ligand-receptor recognition (7,20,21,32). In fact, our observation that bE and bW class II chimeric alleles have specificities different from either parent is not unique to fungal mating-type systems; a similar phenomenon has recently been reported for chimeras of two glycoprotein hormones (4).…”
Section: Figmentioning
confidence: 99%